ANALYSIS OF THE AUTHORITY OF THE SUB-DISTRICT IN THE ERA OF REGIONAL AUTONOMY IN SITINJAU LAUT SUBDISTRICT, KERINCI REGENCY: EFENDI - EFENDI S.Sos., M.Si (JURNAL ADMINISTRASI NUSANTARA, 2022)
Outhority of the district with describe the UU No. 22, 1999 year is update by UU No. 23, 2014 year in reality show district outhority has shifted former head of the region administrative be just as head of the work unit the technical administarive. The authority possessed by the sub-district is currently very limited, which is only limited to the administrative authority of the regional head, and even then with minimalist coverage as well, while the authority given by UU is limited to only a few things and even then only be coordinative. To know the Authority of Subdistrict In the Era of Regional Autonomy In District Sitinjau Laut Kerinci District and Factors what affect the implementation of authority Camat On District Sitinjau Laut Kerinci regency which became the subject matter in this writing is How the Authority of Subdistrict In the Era of Regional Autonomy In District Sitinjau Laut Kerinci Regency. Research using qualitative methods, therefore, the emphasis of structures and individuals as a whole that descriptively describes the state of the subject and object of research based on facts that appear or as it is to find a particular problem carefully. For the selection of informants in this study done purposively (purposive) that is choosing people who are considered to know and able to explain the social phenomena associated with this research. The existence of the Sitinjau Laut Sub-district institution to date is inseparable from the regulatory changes, the re-positioning of the sub-district authority in the era of regional autonomy opens the space for the sub-district / kecamatan institutions to re-exist in the midst of the people who are highly expecting the role of the sub-district to be the only way the community in the affairs of the government assessed by the local community is more effective and efficient when the sub-district / districts institutions get the power that is in accordance with the circumstances and conditions of society in the region. It is advisable to create an independent and sustainable Community The regions provide detailed and in accordance with the needs of the Sitinjau Laut District. The Local Government should review the authority that has been delegated to the District Institution Sitinjau Laut due to the current authority in terms of coordination, guidance and service of whether it is sufficiently capable in madani.